Photoabsorption and quantum efficiency of multi-diameter combined AlxGa1-xN nanostructure UV photodetectors. (15th December 2022) - Lv, Zhisheng; Lu, Feifei; Liu, Lei; Cheng, Hongchang; Zhangyang, Xingyue; Sun, Yan; Guo, Xin
Abstract: In this article, we numerically studied the influence of the geometric structure of the variable Al component Alx Ga1-x N nanowires. In nanowire array photocathodes, the geometrical parameters of the nanowires together with the cross-sectional shape influence the photon trapping effect of the nanostructure and likewise the photon absorption properties of the cathode. We aim to design a variable Al component Alx Ga1-x N nanostructure to obtain optics response optimization for UV photocathode. The simulation results show that the uneven-sized rectangle nanostructure array achieves the best light absorption spectrum of from 300 to 450 nm with an optimal absorption efficiency of 97.47%. Highlights: We aim to optimize the optical response of the AlxGa1-xN photocathode. A multi-radii combination nanostructure of AlxGa1-xN array for UV Photodetectors proposed. The rectangle nanostructure of structure 6 obtains better optical absorption and quantum efficiency. The bottom-up distribution of Al component is 0, 0.087, 0.151, 0.19, and layers thickness is 50 nm, 100 nm, 150 nm, 200 nm.